Exploring the lack of liking for faba bean ingredients with different sensory profiles - Tuccillo, Fabio (Elsevier, 2025)
Faba bean ingredients offer a key role as protein source for wide-ranging food applications, including alternatives to meat and dairy products. However, consumer acceptance is crucial for their integration into people’s diets. This study investigated consumer liking and willingness to use faba bean ingredients and identified the sensory properties that drive consumer preference. Our research involved 264 participants, each with diverse taste abilities, personal attitudes, food choice motives, dietary habits, and demographics. Participants evaluated four pastes made with faba bean ingredients and water in a sensory laboratory setting. Ratings for the liking of smell, taste, overall liking and willingness to use were collected. Additionally, participants evaluated various sensory attributes using Rate-All-That-Apply and Check-All-That-Apply methodologies. To explore the relationships between hedonics, sensory attributes, and participant characteristics, we performed L-PLS regression. Our study revealed that the liking of smell, taste, overall liking, and willingness to use were low for all ingredients, despite their distinct sensory properties. While L-PLS regression did not reveal a distinct pattern of liking, penalty-lift analysis indicated that bitterness was the primary driver of dislike. Moreover, our study identified distinct consumer groups with varying preferences for certain ingredient types. However, considering the overall low-liking scores, the practical relevance of consumer insights might be limited. Our study underscores the interplay between sensory attributes, consumer preferences, and attitudes towards faba bean ingredients. It suggests that addressing bitterness issues could be pivotal in enhancing the market prospects of faba bean ingredients and facilitating their broader acceptance as a protein source.